Effect of lanthanide activated nano‐SiO2 on the corrosion behavior of silane‐based hybrid coatings on low carbon steel. Issue 11 (14th July 2015) - Balan, P.; Chan, E. S.; Harun, M. K.; Swamy, V.; Singh Raman, R. K.
<x xml:space="preserve">Abstract</x> Nano‐silica particles activated with different lanthanide triflates (cerium, lanthanum and yttrium) as fillers in silane sol‐gel coatings were investigated for higher corrosion protection of low carbon steel. Sol‐gel films have been synthesized from cross‐condensation of 3‐glycidoxy‐propyl‐trimethoxy‐silane (3‐GPTMS) and methyl‐triethoxy‐silane (MTES) in acid catalysis condition. The electrochemical behavior of the coated steels was examined by electrochemical impedance spectroscopy (EIS) and potentiodynamic polarization measurements in naturally aerated 0.1 M NaCl solution. The EIS curves suggested that all coatings with nano‐silica and lanthanide triflates within the silane network improved the corrosion performance of low carbon steel, with superior performance by more than two orders of magnitude for 120 hours demonstrated by cerium activated systems. The complementary potentiodynamic polarization studies show similar trends with EIS findings. The coated systems show noble behavior as compared to uncoated steel. The FE‐SEM images in agreement with the electrochemical results indicated that the cerium and lanthanum activated coatings are crack‐free; whereas coatings with yttrium systems are showing defects. Possible inhibiting mechanisms contributing to differences in electrochemical behavior of the coatings with different lanthanides are also discussed.